2018
DOI: 10.1016/j.molmet.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Desacetyl-α-melanocyte stimulating hormone and α-melanocyte stimulating hormone are required to regulate energy balance

Abstract: ObjectiveRegulation of energy balance depends on pro-opiomelanocortin (POMC)-derived peptides and melanocortin-4 receptor (MC4R). Alpha-melanocyte stimulating hormone (α-MSH) is the predicted natural POMC-derived peptide that regulates energy balance. Desacetyl-α-MSH, the precursor for α-MSH, is present in brain and blood. Desacetyl-α-MSH is considered to be unimportant for regulating energy balance despite being more potent (compared with α-MSH) at activating the appetite-regulating MC4R in vitro. Thus, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 46 publications
7
26
1
Order By: Relevance
“…However, a recent study has generated a new mouse model where the cleavage site in ACTH, which is necessary to generate ␣-MSH, has been mutated. By treating these mice with either ␣-MSH or des-acetyl ␣-MSH, it has highlighted the importance of des-acetyl ␣-MSH, by showing it can have an equivalent effect to ␣-MSH in reducing body weight (259).…”
Section: Relative Roles Of ␣-Msh and Its Precursorsmentioning
confidence: 99%
“…However, a recent study has generated a new mouse model where the cleavage site in ACTH, which is necessary to generate ␣-MSH, has been mutated. By treating these mice with either ␣-MSH or des-acetyl ␣-MSH, it has highlighted the importance of des-acetyl ␣-MSH, by showing it can have an equivalent effect to ␣-MSH in reducing body weight (259).…”
Section: Relative Roles Of ␣-Msh and Its Precursorsmentioning
confidence: 99%
“…These findings have recently been challenged by a longer-term study in which both α-MSH and d-α-MSH were genetically deleted from mice, and then individually infused for 14 days at physiological levels into the mouse brain. This study revealed that both peptides could similarly reduce appetite and body weight in male mice 5 . Furthermore, d-α-MSH has been reported to be a more potent agonist of MC4R than α-MSH…”
Section: Discussionmentioning
confidence: 57%
“…S1E). hPSC-derived hypothalamic neurons produce b-MSH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and other POMC-derived peptides…”
Section: Human Hypothalamic Neurons Appropriately Traffic and Secretementioning
confidence: 99%
See 2 more Smart Citations